Sistem informasi geografis untuk pemetaan sebaran kasus tuberkulosis di wilayah kota Manado - Meityn Disye Kasaluhe; Anis Fuad; Riris Andono Ahmad (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Geographic information systems for mapping the distribution of tuberculosis cases in the City of ManadoPurpose: To describe the distribution of TB cases using spatial analysis such as overlay, buffer and cluster in Manado region 2018. Method: This study used survey research with cross sectional approach and Geographic Information System was used in Tuberculosis spreading cases mapping. Spatial clustering by SaTScan 9.6 and mapping by ArcMap 10.4.1.Results: In this study, the number of identifiable TB cases was 475 cases and spread in 10 sub-districts in the Manado region. The area with the highest number of TB cases was Wanea District, which was 112 (23.58%) and the area with few cases was Paal Dua District which was 23 (4.84%). Buffer analysis between the distance of the TB cases and the city center showed that the TB cases mostly had a residence with a distance of 2 km from the city center was 152 (32%). There are 6 clusters of TB cases in the city of Manado. 1st cluster was in Wanea district, 2nd cluster was in Singkil district, 3th cluster was between Malalayang district and Sario district, 4th cluster was located between Tuminting district and Bunaken district, 5th cluster was between Mapanget district and Singkil district, 6th cluster was between Wanea district, Wenang district, Sario district and Paal Dua district. Conclusion: Tuberculosis is a multifactorial disease. Geographical information systems for mapping the distribution of TB cases can be identified in areas that have special characteristics that can support transmission of TB. Mapping of Tuberculosis was expected to help in planning a program to restraint Tuberculosis in the Manado region.